Two Different Clinical Approaches with Mortality Assessment of Four Cases: Complete and Incomplete Type of Abdominal Cocoon Syndrome. (29th January 2020) - Akbas, Ahmet; Hacım, Nadir Adnan; Dagmura, Hasan; Meric, Serhat; Altınel, Yüksel; Solmaz, Ali
Abstract : Abdominal cocoon syndrome (ACS), also called sclerosing encapsulated peritonitis, is a condition characterized by encapsulation of all or some of small bowel loops by a thick fibrous membrane. Etiologic cause is not fully known. It is among the rare causes of intestinal obstruction in adults. Preoperative diagnosis is difficult, and high suspicion is required. Diagnosis is generally made during laparotomy performed due to mechanical obstruction. In treatment of the condition, large scale surgical resections should be avoided. In the present study, we aimed to evaluate all clinical and radiological characteristics and surgical treatment of ACS in light of the literature through four patients operated in our clinic.